PENYEDIAAN MODUL PEMBELAJARAN INOVATIF LARUTAN ELEKTROLIT NONELEKTROLIT MERUJUK MODEL PEMBELAJARAN BERBASIS MASALAH - Ramlan Silaban; Renata Hutagalung; Freddy T.M. Panggabean; Dewi Syafriani (Jurnal Pendidikan Kimia (JPKim), 2014)
Abstract This study aims to compose a innovative electrolyte and non electrolyte learning module and to know its effect on student learning outcomes. The two class student of Xth class from SMA Negeri 7 Medan used as a sample, which both as experimental class teach by  PBL model using innovative modules and control class by original text books. The research data analyzing by descriptive and inferential statistics methods. By this research, we had take an innovative electrolyte and non electrolyte learning module which composed by Borg& Gall procedure and had been standardized  by Indonesian National Standard Education Bureau (BNSP).  The result data show that student learning outcomes of experimental class prestest is 40.75 and postest 79.375 mean score, and control class pretest was 54.37 posttest and  73.875 mean score. Based on rejection of hypothesis show that student learning outcomes which teach by innovative module is higher than using original textbook. Keywords : Innovative learning module, student learning outcomes,  Problem Based Learning